A responsabilidade civil do estado em face dos depósitos irregulares de resíduos sólidos no Estado do Amazonas - Santos, Silvia Helena Antunes Dos (2016)
The epicenter of the search reside in civil Research About State responsibility in face of irregulars Deposits of Solid Waste. Address - will be appreciated the dilemma of Production and solid waste disposal, tracing hum analytical diagnosis of the situation of the Municipal Solid Waste Management in the Amazonian capital, investigating the path traversed hair from Waste Your Descartes Up to a destination, final landfill OS, the que this measure dynamics and the cause of the search problem, the maintenance of landfills toilets, IN Being a consequence, as State measures and private Implementation of opened Guidelines For Law que establishing the National Policy on Solid Waste, and how laws State entailed BY configure the Power - Duty, investigating how environmental impacts resulting possibilities to Political treatment's Issues, paragraph At the end of the TREAT State responsibility in face of legal obligations.